The Tandilia System of Argentina as a southern extension of the Río de la Plata craton: an overview - Cingolani, Carlos Alberto (2010)
The southernmost outcrops of the Río de la Plata cratonic region are exposed in the Tandilia System in eastern Argentina. The geological evolution comprises mainly an igneous-metamorphic Paleoproterozoic basement named Buenos Aires Complex, which is covered by Neoproterozoic to Early Paleozoic sedimentary units which display subhorizontal bedding. The basement of calc-alkaline signature consists mainly of granitic-tonalitic gneisses, migmatites, amphibolites, some ultramafic rocks, and granitoid plutons. Subordinate rock-types include schists, marbles, and dykes of acid and mafic composition. Tandilia was recognized as an important shear belt district with mylonite rocks derived mainly from granitoids. The tectonic scenario seems related to juvenile accretion event (2.25–2.12 Ga) along an active continental margin, followed by continental collision (2.1–2.08 Ga) after U–Pb zircon data. The collisional tectonic setting caused thrusting and transcurrent faulting favouring the anatexis of the crustal rocks. The tholeiitic dykes constrain the time of crustal extension associated with the last stages of the belt evolution. The basement was preserved from younger orogenies such as those of the Brasiliano cycle. After a long paleoweathering process, the Sierras Bayas Group (c. 185 m thick) represents a record of the first Neoproterozoic sedimentary unit (siliciclastic, dolostones, shales, limestones), superposed by Cerro Negro Formation (c. 150–400 m thick, siliciclastics) assigned to Upper Neoproterozoic age. The final sedimentary transgression during Early Paleozoic was the Balcarce Formation (c. 90–450 m thick) deposited over all the mentioned Precambrian units. Based on all the geological background, a tectonic evolution is offered.